FINANCIAL LITERACY, RISK TOLERANCE, RETURN, AND INTEREST IN STUDENT INVESTMENT DECISIONS - Ni Kadek Dita Moon Anggarani (Transpublika Publisher, 2024)
Investing in the capital market is growing rapidly in Indonesia, as evidenced by the increasing number of investors registered at PT Kustodian Sentral Efek Indonesia and most of them are young investors under 30 years old. The objective of this research is to examine how financial literacy, risk tolerance, return, and interest affect decision-making when it comes to investments. The participants involved in this study are students enrolled in the Bachelor of Accounting program at Udayana University's Faculty of Economics and Business from the graduating classes of 2020 and 2021. The sample was determined using the purposive sampling technique, a sample of 242 respondents was obtained. The data analysis technique uses multiple linear regression analysis. The results of the analysis prove that financial literacy, risk tolerance, return, and interest have a positive effect on students' decision to invest. The results of this study can provide empirical support in behavioral finance theory and theory of planned behavior which explain behaviors related to students' decisions to invest.